Pattern Recognition Receptor-Mediated Chronic Inflammation in the Development and Progression of Obesity-Related Metabolic Diseases - Yu, Lili; Li, Yanhua; Du, Cancan; Zhao, Weidong; Zhang, Hanxiao; Yang, Yun; Sun, Aiping; Song, Xiangfeng; Feng, Zhiwei (Mediators of Inflammation, 2019)
Obesity-induced chronic inflammation is known to promote the development of many metabolic diseases, especially insulin resistance, type 2 diabetes mellitus, nonalcoholic fatty liver disease, and atherosclerosis. Pattern recognition receptor-mediated inflammation is an important determinant for the initiation and progression of these metabolic diseases. Here, we review the major features of the current understanding with respect to obesity-related chronic inflammation in metabolic tissues, focus on Toll-like receptors and nucleotide-binding oligomerization domain-like receptors with an emphasis on how these receptors determine metabolic disease progression, and provide a summary on the development and progress of PRR antagonists for therapeutic intervention.